Effect of a Behavioral Support Program on the Social Skills of Male Children With Biomotor Disabilities - Masoume Pourmohamadreza Tajrishi; Roghayeh Tarrah Hamed Nezam; Guita Movallali (University of Social Welfare and Rehabilitation Sciences, 2019)
Objective Children with biomotor disabilities are influenced by negative social attitudes towards themselves; this is due to their problems in independence, self-reliance, and self-help skills. The people's attitudes and children's feedback towards their disability directly influence the adaptation of children. Some support programs can help these children to cope well with different social conditions. A behavioral support program is a new approach to promoting emotional and social competence in children. The program is adjusted as a pyramidal model to support everyone. It focuses on the promotion of health and provides services for children. Moreover, the program replaces appropriate social and communication skills with challenging behaviors (e.g. aggression and rule-breaking) and may improve effective communication and positive behaviors, and reduce negative behaviors in children. The present study aimed to determine the effect of the behavioral support program on the social skills of children with biomotor disabilities in Tehran City, Iran. Materials & Methods This was a quasi-experimental study with a pretest-posttest design and a control group. The study samples consisted of 28 children aged 5-7 years educating in the 2013-2014 academic year in special education centers in Tehran. The sample was purposefully selected. There are only three special centers in Tehran for children with biomotor disabilities. The sample (28 individuals) was selected according to the sample size formula, considering sample missing probability, and the inclusion and exclusion criteria. The subjects consisted of 14, 6 and 8 individuals from the 16th, 5th, and 3rd educational districts, respectively. The students from 16th educational district were allocated in the control group and those from the 5th and 3rd educational districts in the experimental groups. All students in the two experimental groups and control group were matched in terms of socioeconomic status and parent's educational level. Then, the parents and teachers of all groups completed the Social Skills Rating System (SSRS). The students of two experimental groups participated in 14 training sessions (3 days/week; each session: 40 minutes) and received the behavioral support program in addition to the conventional program of the center; the controls only received the center's routine program. Eventually, all parents and teachers of the subjects re-completed the SSRS after the last intervention sessions. The collected data were analyzed by the one-way Analysis of Covariance (ANCOVA).  Results The results of one-way ANCOVA for acquired data from SSRS (parent form) demonstrated that the behavioral support intervention significantly increased (P<0.001) social skills (cooperation, assertiveness, self-control, and responsibility) in male students with biomotor disabilities. According to eta quotients obtained from the parents' evaluation, 82%, 63%, 82%, 66%, and 67% of variations in social skills (cooperation, assertiveness, self-control, and responsibility) of children with biomotor disabilities could respectively be explained by the behavioral support intervention. The results of SSRS (teacher form) revealed that the participation of male students with biomotor disabilities in the intervention has significantly increased their social skills, cooperation, assertiveness, and self-control (P<0.001). Furthermore, according to eta quotients, 65%, 61%, 51%, and 70% of variations in social skills, cooperation, assertiveness, and self-control of male students with biomotor disabilities could be respectively explained by participating in the behavioral support intervention sessions. Conclusion The behavioral support program is a practical strategy for parents and specialists to reduce the social adjustment issues of children with biomotor disabilities. Therefore, the intervention should be considered in planning and policymaking for family training programs. Furthermore, using the behavioral support program along with the conventional training methods can promote social skills, assertiveness, self-control, and responsibility in children with biomotor disabilities. Thus, such programs can prevent ongoing social communication, emotional and academic problems, unemployment, social isolation, and withdrawal, developed due to biomotor limitations in these children.